Comparative Analysis of Indonesia's Human Development Achievements Among ASEAN Countries - Loso Judijanto; Posman WH Hasibuan; Donny Dharmawan; Nirmadarningsih Hiya; Agustinus Nugroho (LPPPIPublishing, 2025)
In a development concept that focuses on humans, development must be carried out in a balanced manner. This balance must be established between building capabilities and utilizing them. This means that human development does not only focus on human capabilities, such as the ability to achieve better health, a longer life, or a higher level of education. This research aims to analyze the comparison of Indonesia's human development achievements among ASEAN countries. This study was conducted through a qualitative comparative study. To help explain this comparative study, secondary data from the United Nations Development Programme regarding the human development index of ASEAN countries from 1990 to 2023 were used. The results show that the comparison of Indonesia's human development achievements through the human development index among ASEAN countries shows a continuous upward trend. Indonesia's human development index ranked 6th out of 11 ASEAN countries in 2023, with a score of 0.73. The highest human development indexes are still held by Singapore and Brunei Darussalam, with scores of 0.95 and 0.84, respectively. Meanwhile, Cambodia and Myanmar have the lowest human development indexes, both with the same score of 0.61.